Dimensi Tasawuf dalam Retorika Dakwah: Refleksi dari Peristiwa Gus Miftah - Syakura, Aflaha Abdan (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
The contemporary da'wah phenomenon displays various communication styles that reflect the social and cultural developments of society, one of which is the rhetorical approach in da’wah combined with Sufi values. Gus Miftah’s da'wah incident has been in the spotlight because of his distinctive rhetoric which is considered eccentric but full of spiritual messages. This study aims to analyze the Sufi dimension in Gus Miftah’s da’wah rhetoric as a reflection of the integration of Islamic mystical values with religious communication strategies in the modern era. The method used is a qualitative-descriptive approach with content analysis techniques on Gus Miftah’s sermons documented in digital media and a library study of classical and contemporary Sufi literature. The results of the study show that Gus Miftah's rhetoric is not only based on persuasive and emotional aspects, but also contains Sufi elements such as the concepts of ikhlas, zuhud, mahabbah, and tazkiyah al-nafs delivered in popular and inclusive language. This strategy has proven effective in reaching marginalized groups who have so far been less touched by conventional da'wah. Gus Miftah employs a Sufi approach in a contemporary context without losing the spiritual essence of Islam, making his preaching not merely informative but also transformational. In conclusion, preaching, incorporating Sufi dimensions through adaptive rhetoric, is able to transcend social barriers and broaden the meaning of preaching as a process of inner enlightenment. These findings demonstrate that Sufism remains relevant as the soul of preaching amidst the dynamics of modern religious communication.